The Impact of Transglobal Leadership Intelligence on Innovative Work Behavior, Work Engagement, Organizational Citizenship Behavior, and Sustainable Tourism Competitiveness: An Empirical Analysis in the Context of Globalization and Organizational Innovation - Adriani Kusuma; Fathorrahman Fathorrahman; Ummi Wahyuni; Nurul Hidayah Ansori; Ayu Maulidia; Zainurrafiqi Zainurrafiqi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study investigates the impact of Transglobal Leadership Intelligence (TGLI) on Sustainable Tourism Competitiveness, focusing on its influence through three mediating variables: Innovative Work Behavior (IWB), Work Engagement (WE), and Organizational Citizenship Behavior (OCB). Conducted in Pamekasan, this research aims to explore how TGLI can enhance the competitiveness of sustainable tourism by fostering innovation, employee engagement, and organizational citizenship within small and medium-sized tourism enterprises (SMEs). A quantitative approach, employing surveys from 190 tourism SME managers in Pamekasan, was used to gather data, which was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study examines the relationships between TGLI and the targeted outcomes to provide a deeper understanding of the mechanisms driving sustainable tourism competitiveness in the context of globalization and organizational innovation. The results indicate that while TGLI positively influences IWB and OCB, it does not significantly affect Sustainable Tourism Competitiveness. Moreover, IWB, WE, and OCB did not show significant direct effects on tourism competitiveness, suggesting that external factors like government policies and resource management play a more dominant role. This research offers valuable insights for tourism SMEs and policymakers, emphasizing the importance of global leadership capabilities and internal organizational dynamics in enhancing sustainable tourism.